2021
DOI: 10.13189/ujer.2021.090201
|View full text |Cite
|
Sign up to set email alerts
|

EFL Instructors and Learners' Perceptions towards Utilization of Online Applications at Palestine Ahliya University and Hebron University

Abstract: After the spread of the Pandemic COVID-19, all educational institutions worldwide shifted to online learning utilizing varied online applications to hold virtual meetings instead of face-to-face ones. Therefore, Palestinian universities used different applications synchronously and asynchronously to manage this sudden and unexpected switch from completely face-to-face mode to an online one. The study aims to investigate the extent to which the online applications utilized in Palestine Ahliya University and Heb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The six reviewed studies (Tirtanawati, 2021;Itmeizeh et al 2021;Baron, 2020;Nartiningrum & Nugroho, 2020;Darsih & Asikin, 2020;and Yulitriana et al, 2020) showed that EFL Students' Perceptions On the Use of Google Meet in Online Learning .........…”
Section: Summary Of Major Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The six reviewed studies (Tirtanawati, 2021;Itmeizeh et al 2021;Baron, 2020;Nartiningrum & Nugroho, 2020;Darsih & Asikin, 2020;and Yulitriana et al, 2020) showed that EFL Students' Perceptions On the Use of Google Meet in Online Learning .........…”
Section: Summary Of Major Resultsmentioning
confidence: 99%
“…The second study (Itmeizeh et al, 2021) showed that students' view of online learning is positive. Students view online learning as flexible and convenient.…”
Section: Students Have Mixed Views On Using Googlementioning
confidence: 96%
See 1 more Smart Citation
“…In the view of Itmeizeh and Farrah (2021), learning is likely to be more effective if online learning is combined with some degree of face-to-face interaction between lecturers and students.…”
Section: Implications Of Covid-19 On Pre-service-teacher Readiness and Preparedness To Teachmentioning
confidence: 99%
“…Students of this generation are accustomed to interacting with one another via social media platforms and do not view one another as senior or junior. Since the advent of online education, numerous educational institutions across the country have incorporated the internet into their teaching and learning processes (Itmeizeh & Farrah, 2021). Datadriven analysis of the implementation of online learning can assist policymakers (schools, government) in streamlining decision-making processes, optimizing resource allocation, monitoring and assisting students experiencing difficulties while online learning, and modifying pedagogical modes and learning methods (Wahyuni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%